MODERN METHODS OF TEACHING ENGLISH AS A FOREIGN LANGUAGE - Turgunova Rano (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This article discusses modern methods of teaching English as a foreign language. The study highlights the importance of interactive and student-centered approaches in language learning. Various teaching methods such as communicative language teaching, task-based learning, and the use of digital technologies are analyzed. The results show that modern methodologies significantly improve students' motivation and communicative competence.